Impact of Feed Point Position on Patch Antenna’s Return Loss and Bandwidth for UWB Applications - Md. Firoz Ahmed; Md. Hasnat Kabir; Abu Zafor Md. Touhidul Islam (Pandawa Institute, 2024)
The demand for compact, lightweight, and high-performance antennas has increased in recent times in the communication industry. Microstrip patch antenna (MPA) becomes a better choice to effectively fulfill these requirements. In this study, hybrid techniques of partial ground plane, slotted patch, and defective ground structure are employed in MPA design to reduce the return loss, good impedance matching, and increased the bandwidth, gain, and efficiency of the antenna. This research demonstrates the impact of altering the feed point position, a crucial phenomenon of antenna design, on the patch antenna and determines the proper feed point location by comparing a minimum return loss (S11) which achieves the highest performance for the designed antenna. High-frequency structure simulator (HFSS) software is used to design and simulate the patch antenna. The operating frequency of the antenna is 6.85 GHz for UWB applications (3.1–10.6 GHz). A FR4 epoxy substrate material with dimensions of 30 mm × 20 mm is used to design the antenna. It has a dielectric constant of 4.4, a thickness of 0.8 mm and a tangent loss of 0.02. Multiple resonant frequencies are observed with different return losses for each feed location. The analysis shows that the finest feeding point is found at the center of the patch (9, 0) with a very low return loss (-28.35 dB), and a high impedance bandwidth (19.7 GHz). The antenna also achieved a gain of 4.46 dB, a directivity of 4.6904 dB, and a radiation efficiency of 95.90%. Hence, the location of the feed point can be considered as an influential factor in the antenna design.